2017
DOI: 10.1038/s41559-017-0375-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic consequences of intensive inbreeding in an isolated wolf population

Abstract: Inbreeding (mating between relatives) is a major concern for conservation as it decreases individual fitness and can increase the risk of population extinction. We used whole-genome resequencing of 97 grey wolves (Canis lupus) from the highly inbred Scandinavian wolf population to identify 'identical-by-descent' (IBD) chromosome segments as runs of homozygosity (ROH). This gave the high resolution required to precisely measure realized inbreeding as the IBD fraction of the genome in ROH (F ). We found a striki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
249
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(286 citation statements)
references
References 53 publications
24
249
0
Order By: Relevance
“…Our results show similar phenomenon to some other populations (wild wolves and laboratory planarians) that show heterozygosity throughout the genome despite many generations of inbreeding (Kardos et al., ) or selfing (Guo et al., )—though not clonal propagation as in the clone. However, it is important to note that the mating system of the honey bee differs markedly from these previously studied species.…”
Section: Discussionsupporting
confidence: 90%
“…Our results show similar phenomenon to some other populations (wild wolves and laboratory planarians) that show heterozygosity throughout the genome despite many generations of inbreeding (Kardos et al., ) or selfing (Guo et al., )—though not clonal propagation as in the clone. However, it is important to note that the mating system of the honey bee differs markedly from these previously studied species.…”
Section: Discussionsupporting
confidence: 90%
“…Looking to the future, although ours and many other studies have quantified heterozygosity using microsatellites, simulations clearly indicate that tens of thousands of markers will outperform even very deep pedigrees at capturing inbreeding depression, particularly when they can be mapped to a reference genome to quantify ROH (Kardos et al., ; Wang, ). This is supported by a growing number of empirical studies of wild populations using approaches like restriction site‐associated DNA sequencing (Hoffman et al., ), high density SNP arrays (Chen et al., ; Huisman et al., ) and whole‐genome resequencing (Kardos et al., ). As the costs of these and related methods continue to fall, they are likely to become preferred approaches for studying inbreeding and its consequences in wild populations.…”
Section: Discussionmentioning
confidence: 99%
“…We have already mentioned hidden Markov models. Similarly, Kardos et al (2018), for example, measured inbreeding in Scandinavian wolves from "identical-by-descent" chromosome segments (runs of homozygosity), and also found that these estimates correlated surprisingly well with pedigree data and with estimates obtained from 500 single nucleotide polymorphisms (SNPs). Focusing on inbreeding rather than effective size could also help modelling in some situations.…”
Section: Beyond Effective Sizementioning
confidence: 94%